Analysis of precursor information for coal and gas outbursts induced by roadway tunneling: A simulation test study for the whole process. (April 2022) - Wang, Hanpeng; Zhang, Bing; Yuan, Liang; Wang, Su; Yu, Guofeng; Liu, Zhongzhong
Highlights: The whole process of outburst was completely reproduced by a simulation test. The abnormal characteristics of key contact indicators before outburst were detected. The sensitivity priorities of outburst precursor information in the process of uncovering coal was obtained. The variation parameters of the key contact indicators had more advantages than the signal itself. Abstract: The diversity of precursor information is significant for providing accurate early warnings of outbursts. However, the existing research mainly focuses on noncontact indicators, which cannot fully and accurately reflect the outburst risk. To capture the precursor information of the key contact indicators, a simulation test for the whole process of outbursts was carried out. In the test, the newly developed similar materials of gassy coal and ultralow permeability rock and a simulation system were used to simulate the occurrence environment and disturbance conditions of the coal mass. The results show that the outburst phenomenon and gas concentration evolution are similar to the real phenomenon on site, which proved the accuracy of the test results. The abnormal characteristics of a number of physical aspects before outburst were detected: an obvious relief stress zone appeared in the in situ stress curve for coal seam; the gas concentration in the roadway exceeded the safety standard (0.3%) and continued to increase to 3%; the pressure of coal seam and roadway surrounding rock changed from stable to declining, with a total amplitude of 10 kPa; the temperature in coal seam and roadway changed from steady to fluctuating up and down, with fluctuations reaching 3.4 °C and 4.7 °C, respectively. According to the abnormal occurrence time and identification level, the sensitivity priorities of the above information were temperature, gas concentration, in situ stress, and gas pressure. In addition, the moving average, deviation rate, and dispersion rate of the gas concentration, gas pressure, and temperature versus time curve had more advantages than the signal itself. This study provides guidance for the realization of accurate and effective real-time warnings.